Overestimated labor force potential in Germany: The role of flexible working time models - Christina Heike Maaß (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2024)
With economists suggesting to increase labor market participation to counter demographic changes and skills shortages, contrary to the recently increased awareness of work-life balance, the question arises as to how much of the previously unexploited labor supply can actually be activated and pushed into full-time positions. In this paper, we empirically analyze the intentions of the underemployed and inactive individuals based on a sound theoretical analysis. By firstly exploring responses to the EU Labor Force Survey and the German microcensus, we find changes in labor supply behavior over time. The results are corroborated and extended by novel search data from Google Trends, which provide further details on the increasing preferences for fewer working hours and part-time work implicitly expressed via the search engine. We identify the overestimation of the labor force potential in Germany to be substantial and realistically assume a limited potential to activate the unexploited workforce.
Keywords: 330